2016
DOI: 10.1371/journal.pone.0158997
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Cultured Mesothelial Cells Derived from the Murine Adult Omentum

Abstract: The human omentum has been long regarded as a healing patch, used by surgeons for its ability to immunomodulate, repair and vascularise injured tissues. A major component of the omentum are mesothelial cells, which display some of the characteristics of mesenchymal stem/stromal cells. For instance, lineage tracing studies have shown that mesothelial cells give rise to adipocytes and vascular smooth muscle cells, and human and rat mesothelial cells have been shown to differentiate into osteoblast- and adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…Previously it was shown that mouse prMC may be cultured for more than 25-30 passages, until the symptoms of senescence become visible (22). Importantly, during this time period a subset of cells were shown to express stem cell markers such as Sox9, Sox2, CD34, Bmi1 and these cells showed adipogenic and osteogenic differentiation potential in vitro (22). This strongly indicates the presence of a prMC subpopulation with stem cell properties.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously it was shown that mouse prMC may be cultured for more than 25-30 passages, until the symptoms of senescence become visible (22). Importantly, during this time period a subset of cells were shown to express stem cell markers such as Sox9, Sox2, CD34, Bmi1 and these cells showed adipogenic and osteogenic differentiation potential in vitro (22). This strongly indicates the presence of a prMC subpopulation with stem cell properties.…”
Section: Discussionmentioning
confidence: 95%
“…Based on the elevated Sox2/Oct4 levels necessary to drive eGFP expression, the eGFP(+) prMC might be cautiously assumed to also represent a cell population with stem cell properties. Previously it was shown that mouse prMC may be cultured for more than 25-30 passages, until the symptoms of senescence become visible (22). Importantly, during this time period a subset of cells were shown to express stem cell markers such as Sox9, Sox2, CD34, Bmi1 and these cells showed adipogenic and osteogenic differentiation potential in vitro (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is not clear whether postnatal or even adult mesothelial cells in the peritoneal cavity generally contribute to the maintenance of the intestinal and parietal body wall. This is pertinent because of reports suggesting that mesothelial cells have the plasticity to differentiate into cells of different mesodermal lineages (Colunga et al, 2019, Karki et al, 2014, Mutsaers et al, 2015, Dauleh et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…La baja expresión de marcadores HLA tipo I y II y la ausencia de algunas moléculas co-estimuladoras como CD80, CD86 y CD40 ha favorecido su uso alogénico en diferentes patologías por su baja inmunogenicidad. Sin embargo, existe cierta controversia en la literatura sobre si el proceso de diferenciación a otras estirpes celulares favorece la expresión de marcadores HLA (15)(16)(17)(18)(19)(20).…”
Section: Introductionunclassified